Enhancing Profitability in Retail Companies: An Analysis of Turnover, Sales Growth, and Capital Structure - Setiawan, Bagas; Zaretta, Bara; Yovita, Lenni; Setyahuni, Suhita Whini (Finance : International Journal of Management Finance, 2025)
This research seeks to unveil the influence of cash turnover, inventory turnover, receivables turnover, sales growth, and capital structure on the profitability of retail trade sub-sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The study was conducted to determine how retail operations generate profitability. The total sample of this study is 21 retail sub-sector companies through purposive sampling, with a 5-year observation period from 2019-2023. So, there are 105 sample financial performances used in this research. The analysis tool is E-views 12 with the panel data approach. Random Effect Model is selected because it meets the criteria for BLUE test panel data. Cash (CTO) and inventory turnover (ITO) are two variables that cannot meet the effect on profitability, meanwhile the receivable turnover (RTO), sales growth (SGR) and capital structure proxied by DER can affect profitability partially. The simultaneous testing shows that cash turnover, inventory turnover, receivables turnover, sales growth, and capital structure have a significant effect on profitability.